World and oil in the 1990s : need for realism. - Olorunfemi, Michael A. (1991)
Reviews the forces that fed instability of oil prices in the 1980s. Examines policy orientation in the consuming countries to determine how much conservation and oil substitution is still possible in the light of environmental concern and energy dependence, stabilization policy and the desire to sustain a high economic growth rate. Identifies possible areas of convergence between the interest of the consumers and that of producers.